A Nonenzymatic Glucose Sensor Based on the Excellent Dispersion of a Graphene Oxide-Poly(acrylic acid)-Palladium Nanoparticle-Modified Screen-Printed Carbon Electrode. Issue 13 (7th August 2019) - Samoson, Kritsada; Thavarungkul, Panote; Kanatharana, Proespichaya; Limbut, Warakorn
Abstract : An electrochemical sensor consisting of a screen-printed carbon electrode (SPCE) modified with graphene oxide-poly(acrylic acid)-palladium nanoparticles (GO-PAA-PdNPs) was developed for the nonenzymatic determination of glucose by flow injection amperometry (FI-Amp). PdNPs were synthesized on GO-PAA by electroless deposition. The surface morphology of the modified electrode was characterized by transmission electron microscopy (TEM) and Fourier transform infrared (FT-IR) spectroscopy. The electrochemical behavior of glucose on the different modified surfaces was studied by cyclic voltammetry and amperometry. The GO-PAA-PdNPs-modified SPCE showed excellent electrocatalytic performance for the oxidation of glucose. To achieve the optimal electrocatalytic oxidation of glucose by the GO-PAA-PdNPs/SPCE, the applied potential, sample volume and flow rate of the FI-Amp system were optimized. Under the optimal conditions, the current response when the glucose standard was injected provided a detection limit of 22 μmol L −1, a limit of quantitation of 76 μmol L −1 and two linear ranges, 50 to 15, 000 μmol L −1 and 15, 000 to 60, 000 μmol L −1 . This sensor had excellent sensitivity as well as good repeatability and selectivity. The sensor was applied to detect glucose in biological fluid samples, and the results were in good agreement with those obtained by the standard hexokinase-spectrophotometric method.